Design of a water distribution system for proposed BDC Housing Development Scheme at Block 8 Klauh Land district, Sri Aman Division - Chong, G.S.C (University Malaysia Sarawak, (UNIMAS), 2000)
This dissertation is about the design of the system for the proposed BDC Housing Development Scheme at Block 8 Klauh Land District, Sri Aman Division.